2022
DOI: 10.1109/tim.2022.3164166
|View full text |Cite
|
Sign up to set email alerts
|

A 4-D Ultrasound Tomography for Industrial Process Reactors Investigation

Abstract: A volumetric ultrasound tomography (UST) system and method are established for industrial process applications. A twoplane ring-array UST system is developed for 3D imaging of the process under test. Such a 3D system allows capturing axial variations, which is not possible in 2D or 2.5D imaging. A ray-voxel intersection method is used to create the sensitivity matrix needed for the 3D or 4D image reconstruction. Acquiring and processing time series data lead to 4D imaging, generating dynamical volumetric image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…Where 𝜟𝜟𝜟𝜟 is the reconstructed distribution based on acoustic features, A is the modeling operator, which expresses the sensitivity distribution in the FOV, 𝜟𝜟𝜟𝜟 is the sensor's recorded data, and 𝒆𝒆 is the noise in the measurements. A ray-based method was used to generate the sensitivity matrix, as shown in [11]. A simplified inversion can be done using back projection.…”
Section: B Ust Hardwarementioning
confidence: 99%
See 1 more Smart Citation
“…Where 𝜟𝜟𝜟𝜟 is the reconstructed distribution based on acoustic features, A is the modeling operator, which expresses the sensitivity distribution in the FOV, 𝜟𝜟𝜟𝜟 is the sensor's recorded data, and 𝒆𝒆 is the noise in the measurements. A ray-based method was used to generate the sensitivity matrix, as shown in [11]. A simplified inversion can be done using back projection.…”
Section: B Ust Hardwarementioning
confidence: 99%
“…There are no experimental studies related to lung UST imaging. This is despite great progress made in further advancement of the UST devices and algorithms in past few years [11][12][13][14]. A simulations study of thorax UST was shown in [15].…”
mentioning
confidence: 99%